The effect of Ni and Fe on the decomposition of yttrium doped barium zirconate thin films. (August 2021) - Jennings, Dylan; Ricote, Sandrine; Caicedo, José Manuel; Santiso, José; Reimanis, Ivar
Abstract: Transition metal dopants like Ni and Fe are known to influence the densification and microstructure evolution of yttrium doped barium zirconate (BZY), and understanding their behavior impacts the use of BZY in applications like protonic ceramic fuel cells and catalysts. This work investigates the effects of Ni and Fe on the evolution of BZY thin films in high temperature (1175°C), reducing environments, where BZY faceting and decomposition is observed. It is shown that the addition of Ni promotes film decomposition, whereas Fe prevents decomposition. The effects of the dopants on film decomposition are consistent with thermodynamic predictions that indicate the addition of Fe to the B-site of the perovskite structure diminishes the Gibbs free energy change for decomposition. Graphical abstract: Image, graphical abstract